Pelantihan dan Pengabdian Masyarakat Keterampialan Menulis Lontar - Widiana, I Wayan (JURNAL WIDYA LAKSANA, 2016)
abstrakIn attempt to erase poverty and reducing unemployment people in the society, it is very important to have a high self-awareness and motivation from the people, not only producer but also the consumers as the users of Lontar (Palm Leaves) Writing Skill result.            The Life Skill Education is aiming the improvement of the human resources quality by giving Lontar Writing Skill training for people who don’t have chance to have a formal education and those who have minimum knowledge and skill, so they can make their own work field which basically will make their life become better. In order to give those people an helpful skill that will make them having a better life, it’s very important to give Lontar Writing Skill training for the society in Tianyar village, Kubu Sub district, Karangasem Regency.            The method is used in this activity is seminar and workshop by involving 15 untill 25 years old productive people. The main product of this activity is (1) The society will be able to write lontar in a good way. (2) The society start to learn writing lontar at home by them self. (3) Knowing the lontar writing technique so that they can write it well. (4) Knowing the best marketing technique to use. (5) The society start to think creatively, innovatively, and to be a lontar writer.Keywords: Training, Writing Lontar Skill